Evaluation on Instructional Management of Islamic Education in Adiwiyata School - Rofiq Hidayat (STAI Ma'had Aly Al-Hikam Malang, 2020)
This study aimed to describe more deeply about the evaluation of learning in the 2013 curriculum conducted by the teachers of Islamic education in Adiwiyata School Program. Approaches of this research using qualitative approach, was designed is a case study research. The location were selected is SMAN 5 Jember. Based on the research and the study found that in general the management of Islamic Education learning in SMAN 5 Jember has followed the steps of principles and management functions. Evaluation of learning to do with essays for cognitive and non-test for psychomotor and affective aspects, but specifically for affective use some additional instruments such as a form prepared by the central education authorities. In an effort to enhance the instructional management better, this study suggested should improve the control or supervision of the administration on PAI teacher performance, innovations on the Islamic education learning management.